Development of reactive control strategy for multi-agent mobile robotics system - Ahmad, Mohd. Ridzuan (Penerbit UTM Press, 2001)
Multi-agent system is one the most popular research interests in robotics nowadays. Imagine for a swarm of robots, what kind of intelligence can we build now? This question arises from emulating biological systems. How is it that colonies of small ants can work together to perform a difficult task that single ant cannot do it alone? How might collections of simple robots aid us in human endeavours? By examining these questions, one of the common characteristics shared by each agent is in agent simplicity. Simplicity in control means that the robots are provided with direct commands in order to execute the action. It doesn't need to gather all information from various sensors to plan its action like deliberative control which is also known as sensors fusion that clearly required a lot of computational time and also the mapping that its produces might not valid at the time when changes occurs between the time it gathers the information and the time it plans its actions. Instead, intelligence will arise when these simple agents work together to perform some complex task cooperatively. By examining the major control architectures available in robotics area, subsumption-based reactive control architecture gives the tools as required. Priority-based scheme is used in arbitration level to select which behaviour to run. In this paper decentralised reactive control architecture was used to justify the communication based simple control architecture can perform complex task like carrying load and navigate.